Development of Bingo Wheel Learning Media on Class X Zakat Fitrah Material at Madrasah Aliyah - Fadillah, Anggun; Sukirman, Sukirman; Alam, Kharisma (Educational Journal of Learning Technology, 2024)
This research took place using a qualitative approach and a quantitative approach. This type of research is Research and Development (R&D) with research procedures and designs using the ADDIE development model, including Analytics, Design, Development, Implementation, and Evaluation. This research was conducted at Madrasah Aliyah Al-Falah Lemahabang and produced a Bingo Wheel learning media product. The data collection techniques used are interviews, questionnaires, tests, and documentation. The validity of the data was carried out by qualitative descriptive analysis and quantitative descriptive analysis. The results of the data analysis show that: 1) The procedure for the development of Bingo Wheel learning media on zakat fitrah material class X at Madrasah Aliyah Al-Falah Lemahabang is carried out with the ADDIE development model, namely Analisys, Design, Development, and Implementation. 2) Validity of Bingo Wheel learning mediain the material of zakat fitrah class X at Madrasah Aliyah Al-Falah Lemahabang by media experts obtained a percentage result of 90% and by material experts obtained a percentage result of 96.4%. 3) The practicality of the Bingo Wheel learning media on the Class X zakat fitrah material at Madrasah Aliyah Al-Falah Lemahabang got a percentage result of 93.3% from the subject teacher and by students got a percentage result of 89.8%. 4) The effectiveness of the Bingo Wheel learning media on the Class X zakat fitrah material at Madrasah Aliyah Al-Falah Lemahabang based on the results of the pre-test score got a completion percentage of 32.3% with an average of 58.8 and the results of the post-test score got a completion percentage of 100% with an average of 88.6 so that it can be concluded that the development of Bingo Wheel learning media in improving the learning achievement of students in class X of Madrasah Aliyah Al-Falah Lemahabang is very effective in use.